1992
DOI: 10.1101/gad.6.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Stable nucleosome positioning and complete repression by the yeast alpha 2 repressor are disrupted by amino-terminal mutations in histone H4.

Abstract: Nucleosomes ate positioned in the presence of the yeast repressor a2 in minichromosomes containing the a2 operator and on the promoters of a-cell-specific genes regulated by a2. To investigate the possibility that al directs nucleosome position through an interaction with a component of the core particle, we analyzed chromatin structures adjacent to the operator in a cells containing mutations in the amino-terminal region of histone H4. Deletion or point mutation of specific amino acids in histone H4 altered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
119
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 153 publications
(127 citation statements)
references
References 53 publications
8
119
0
Order By: Relevance
“…This is strongly supported by the observation that a deletion of the histone H2B cross-linking domain changes the minichromosome topology in vivo, suggesting that this domain is required for the proper folding of DNA in the nucleosome (63). Deletion or substitution of a single amino acid in the cross-linking domain of histone H4 alters chromatin structure in vivo (63)(64)(65)(66), decreases the ability of yeast to mate, increases the duration of S phase (67)(68)(69)(70), and affects telomeric repression (71,72) as well as expression of a large number of yeast genes (64,65,(73)(74)(75). It should be mentioned also that the cross-linking domain of histone H4 contains sites for post-translational acetylation and phosphorylation (76) that may also be involved in the regulation of the interaction of this domain with DNA at different levels of chromatin activity and condensation rendering nucleosomes competent for transcription and/or replication.…”
Section: The Change In Histone H2b/h4-dna Contacts Induced By Low Ionsupporting
confidence: 48%
“…This is strongly supported by the observation that a deletion of the histone H2B cross-linking domain changes the minichromosome topology in vivo, suggesting that this domain is required for the proper folding of DNA in the nucleosome (63). Deletion or substitution of a single amino acid in the cross-linking domain of histone H4 alters chromatin structure in vivo (63)(64)(65)(66), decreases the ability of yeast to mate, increases the duration of S phase (67)(68)(69)(70), and affects telomeric repression (71,72) as well as expression of a large number of yeast genes (64,65,(73)(74)(75). It should be mentioned also that the cross-linking domain of histone H4 contains sites for post-translational acetylation and phosphorylation (76) that may also be involved in the regulation of the interaction of this domain with DNA at different levels of chromatin activity and condensation rendering nucleosomes competent for transcription and/or replication.…”
Section: The Change In Histone H2b/h4-dna Contacts Induced By Low Ionsupporting
confidence: 48%
“…Analysis of deletions and single amino acid changes in the N-terminal region of histone H4 has demonstrated that certain changes in the H4 N terminus abolish repression of the yeast silent mating-type cassettes (35,36; see reference 25 for a review). Some of these H4 mutants also prevent efficient repression by the ␣2 repressor (60) and repression of genes adjacent to telomeres (2). Similar analysis has shown that deletion of a different but overlapping N-terminal region of H4 prevents efficient activation of the GAL1 and PHO5 genes (22), while deletions in the N-terminal tail of histone H3 lead to hyperactivation of the GAL1 gene (43).…”
mentioning
confidence: 63%
“…Previous work has established that the MAT~2 repressor precisely positions an array of nucleosomes adjacent to its operator and has suggested that this nucleosome positioning plays an important role in the mechanism of transcriptional repression by MATe~2 (Shimizu et al 1991;Roth et al 1992). Because SSN6 and TUP1 are required for full repression of a cell-specific gene expression (Keleher et al 1992), we reasoned that these proteins might be involved in MAT~2-mediated nucleosome positioning.…”
Section: Resultsmentioning
confidence: 99%